Analisis Dan Perancangan Sistem Informasi Pemesanan Kamar Hotel Berbasis Web Pada Hotel Auliya - Arrahman, Naqif; Mulyono, Herry (Jurnal Manajemen Sistem Informasi, 2021)
Problems that occur to this day at the hotel Auliya was the lack of an information system that can perform the recording of hotel booking and managing data electronically and lack of information for the hotel pemasaaran Auliya. The purpose of this research was to analyze and design the room booking system, manage data, marketing and reporting automatically each month. This research method either using UML (Unified Modeling Language) to design the system. This research resulted in the design of the hotel reservation information system to manage data, information and reporting is automated. This plan could be developed into an application that can be implemented, as well as expected this research can be a reference and learning especially in the field of information systems.